The Interaction Between Civil Society And Public Authorities In Ukraine: Information And Telecommunication Dimension - IRYNA, MYLOSERDNA; ALEVTINA, PEKHNYK; ALINA, PROKHORENKO; KATERYNA, SAVON (The journal of contemporary issues in business and government, 2021)
The article deals with the study of the peculiarities of interaction between civil society and public authorities in the conditions of intensification of information and telecommunication technologies in Ukraine, which is the foundation for the formation of new ways of external reflection of civil society participation in state and municipal issues. The purpose of the article is to determine areas for improving the practice of interaction between civil society and public authorities; defining the concept of state power in accordance with the updated principles of democratization and globalization, determining specific recommendations for reforming the existing system of state regulation in Ukraine. The methodological basis of this article is a set of general and special methods of scientific knowledge: systematic analysis method, dialectical method, formal-logical method and structural-functional method and a number of empirical methods. The authors substantiate the forms of interaction between civil society and public authorities, which is institutionalized in: a) formal field in the form of: appeals of citizens to public authorities; public examination of the activities of public authorities; anti-corruption public examination of public authorities; functioning of public (expert) councils at public authorities, etc.; b) practical field through the provision of public services; consideration of citizens’ appeals; functioning of the National portal of open data and electronic systems Prozorro, etc. To determine the current state of interaction between public authorities and civil society in the implementation of information and telecommunication technologies, it has been studied: specifics of the introduction of the idea of digital state in Ukraine as a condition for determining new interaction forms between civil society and public authorities; international standards, which define the principles of use of information and telecommunication technologies in relations between public authorities and civil society; specifics of providing electronic public services and consideration of electronic appeals of citizens. The article can be useful for practitioners and officials of the administrative apparatus, and also citizens with the appropriate level of legal conscience. In addition, certain aspects of the study can be used in subsequent developments in the socio-political field, the subject of which regards to the functioning of civil society. The novelty and originality of the study is that the article highlights the features of interaction between civil society and public authorities, under the circumstances the tendency of intensification of the use of information and telecommunication technologies.